El régimen jurídico de la acuicultura en el Perú - Ramos Huaytalla, Bruno (2022)
Aquaculture is an economic activity regulated by Peruvian law, the purpose of which is to cultivate aquatic species and ensure the conservation of biodiversity. In this article, the authors start by analyzing the current regulations on hydrobiological resources and then identify the regulation of aquaculture activity, as well as the administrative sanctioning procedure applicable to non-compliance with aquaculture, environmental and sanitary obligations derived from that activity.